A case for corpus stylistics: Ian Fleming's Casino Royale - Mahlberg, Michaela; McIntyre, Dan (English Text Construction, 2011)
In this article we investigate keywords and key semantic domains in Fleming's Casino Royale. We identify groups of keywords that describe elements of the fictional world such as characters and settings as well as thematic signals. The keyword groups fall into two broad categories that are characterized as text-centred and reader-centred, with the latter providing particular clues for interpretation. We also compare the manually identified keyword groups with key semantic domains that are based on automatic semantic analysis. The comparison shows, for instance, how words that do not seem to fit a semantic domain can be seen as reader-centred keywords fulfilling specific textual functions. By linking our analysis to arguments in literary criticism, we show how quantitative and qualitative approaches can usefully complement one another. © John Benjamins Publishing Company.
CRIS-Team Scopus Importer:2024-03-27

Analysing the opinions of UK veterinarians on practice-based research using corpus linguistic and mathematical methods - Huntley, Selene J.; Mahlberg, Michaela; Wiegand, Viola; van Gennip, Yves; Yang, Hui; Dean, Rachel S.; Brennan, Marnie L. (Preventive Veterinary Medicine, 2018)
The use of corpus linguistic techniques and other related mathematical analyses have rarely, if ever, been applied to qualitative data collected from the veterinary field. The aim of this study was to explore the use of a combination of corpus linguistic analyses and mathematical methods to investigate a free-text questionnaire dataset collected from 3796 UK veterinarians on evidence-based veterinary medicine, specifically, attitudes towards practice-based research (PBR) and improving the veterinary knowledge base. The corpus methods of key word, concordance and collocate analyses were used to identify patterns of meanings within the free text responses. Key words were determined by comparing the questionnaire data with a wordlist from the British National Corpus (representing general English text) using cross-tabs and log-likelihood comparisons to identify words that occur significantly more frequently in the questionnaire data. Concordance and collocation analyses were used to account for the contextual patterns in which such key words occurred, involving qualitative analysis and Mutual Information Analysis (MI3). Additionally, a mathematical topic modelling approach was used as a comparative analysis; words within the free text responses were grouped into topics based on their weight or importance within each response to find starting points for analysis of textual patterns. Results generated from using both qualitative and quantitative techniques identified that the perceived advantages of taking part in PBR centred on the themes of improving knowledge of both individuals and of the veterinary profession as a whole (illustrated by patterns around the words learning, improving, contributing). Time constraints (lack of time, time issues, time commitments) were the main concern of respondents in relation to taking part in PBR. Opinions of what vets could do to improve the veterinary knowledge base focussed on the collecting and sharing of information (record, report), particularly recording and discussing clinical cases (interesting cases), and undertaking relevant continuing professional development activities. The approach employed here demonstrated how corpus linguistics and mathematical methods can help to both identify and contextualise relevant linguistic patterns in the questionnaire responses. The results of the study inform those seeking to coordinate PBR initiatives about the motivators of veterinarians to participate in such initiatives and what concerns need to be addressed. The approach used in this study demonstrates a novel way of analysing textual data in veterinary research.
CRIS-Team Scopus Importer:2024-03-27
Keywords: Corpus linguistic analysis; Corpus linguistics; Evidence-based veterinary medicine; Practice-based research; Questionnaire; Survey; Topic modelling; Veterinarian; Veterinary surgeon

Applied Digital Humanities: Calling for a more engaged Digital Humanities - Glawion, Anastasia; Lang, Sabine; Kremer, Dominik; Mahlberg, Michaela; Wagner, Andreas (Digital Humanities im deutschsprachigen Raum (DHd), 2025)
Keywords: Applied Digital Humanities; engagement

CLiC Dickens: Novel uses of concordances for the integration of corpus stylistics and cognitive poetics - Mahlberg, Michaela; Stockwell, Peter; De Joode, Johan; Smith, Catherine; O'Donnell, Matthew Brook (Corpora, 2016)
This paper introduces the web application CLiC, which we developed as part of a research project bringing together insights from both cognitive poetics and corpus stylistics, with Dickens's novels as a case study. CLiC supports the analysis of discourse in narrative fiction with search options that make it possible to focus on stretches of text within and outside quotation marks. We argue that such search options open up novel ways of using concordances to link lexico-grammatical and textual patterns. We focus specifically on patterns for the creation of fictional characters. From a technical point of view, we explain the XML annotation that CLiC works with. Our discussion of textual examples focusses on phrases in fictional speech that illustrate significant differences between text within and outside quotation marks. In terms of theory, we argue that CLiC supports the identification of textual patterns that can provide insights into fictional minds and contribute to the exploration of readerly effects within the wider framework of mindmodelling.
CRIS-Team Scopus Importer:2024-03-27
Keywords: Characterisation; Dickens; Fictional speech; Mind-modelling; Suspensions

Corpus linguistics and discourse analysis - Mahlberg, Michaela (De Gruyter, 2014)
CRIS-Team Scopus Importer:2024-03-27

Corpus linguistics and the study of nineteenth-century fiction - Mahlberg, Michaela (Journal of Victorian Culture, 2010)
CRIS-Team Scopus Importer:2024-03-27

Corpus Linguistics, Context and Culture - Wiegand, Viola; Mahlberg, Michaela (De Gruyter, 2019)
Corpus Linguistics, Context and Culture demonstrates the potential of corpus linguistic methods for investigating language patterns across a range of contexts. Organised in three sections, the chapters range from detailed case studies on lexico-grammatical patterns to fundamental discussions of meaning as part of the ‘discourse, contexts and cultures’ theme. The final part on ‘learner contexts’ specifically emphasises the need for mixed-method approaches and the consideration of pedagogical implications for real world contexts. Beyond its contribution to current debates in the field, this edited volume indicates new directions in cross-disciplinary work.
CRIS-Team Scopus Importer:2024-03-27

Corpus stylistics and Dickens's fiction - Mahlberg, Michaela (Taylor and Francis, 2013)
This book presents an innovative approach to the language of one of the most popular English authors. It illustrates how corpus linguistic methods can be employed to study electronic versions of texts by Charles Dickens. With particular focus on Dickens’s novels, the book proposes a way into the Dickensian world that starts from linguistic patterns. The analysis begins with clusters, i.e. repeated sequences of words, as pointers to local textual functions. Combining quantitative findings with qualitative analyses, the book takes a fresh view on Dickens’s techniques of characterisation, the literary presentation of body language and speech in fiction. The approach brings together corpus linguistics, literary stylistics and Dickens criticism. It thus contributes to bridging the gap between linguistic and literary studies and will be a useful resource for both researchers and students of English language and literature.
CRIS-Team Scopus Importer:2024-03-27

Corpus Stylistics and the Pickwickian watering-pot - Mahlberg, Michaela (Bloomsbury Publishing Plc., 2009)
CRIS-Team Scopus Importer:2024-03-27

Corpus Stylistics - Mahlberg, Michaela (Bloomsbury Publishing Plc., 2015)
CRIS-Team Scopus Importer:2024-03-27

Corpus stylistics - Dickens, text-drivenness and the fictional world - Mahlberg, Michaela (Dickens and Modernity, 2012)
CRIS-Team Scopus Importer:2024-03-27

Corpus stylistics, norms and comparisons: Studying speech in great expectations - Mahlberg, Michaela; Wiegand, Viola (Taylor and Francis, 2018)
This chapter situates corpus stylistics within wider trends in the digital humanities and emphasises the need for developing tools and visualisation methods tailored to the analysis of literary texts. Using the CLiC web app, the chapter shows how standard corpus linguistic methods can be further developed to better address research questions in literary stylistics. The analysis presents an innovative comparative approach to the identification of speech clusters in an individual fictional text-Dickens’s Great Expectations-as compared to larger corpora containing all of Dickens’s novels and authentic spoken language, respectively. This comparative perspective does not only emphasise differences between fictional speech and narration, but also considers overlapping patterns. The chapter links the notions of deviation and norms that are drawn on in literary stylistics to corpus linguistic comparisons of different corpora with particular emphasis on the fuzzy nature of linguistic categories.
CRIS-Team Scopus Importer:2024-03-27

Defining the Carceral Characteristics of the ‘Dickensian prison’: A Corpus Stylistics Analysis of Dickens’s Novels - March, Eleanor; Moran, Dominique; Houlbrook, Matt; Jewkes, Yvonne; Mahlberg, Michaela (Victoriographies, 2023)
Charles Dickens is often evoked to make connections to Victorian times – and to highlight the need for change in today’s society. The situation of prisons is a prime example, where references to the ‘Dickensian prison’ figure in contemporary discourse to draw critical attention to the state of prisons and to call for reform. But it would be too simple to assume that today’s references to the Dickensian prison relate directly to the way Dickens narrates the prison. Therefore, this paper presents a detailed digital humanities textual study of prisons in Dickens’s novels to shed light on the vocabulary that the author uses to talk about this institution. The prisons in Dickens’s novels tend to be historic and outdated prisons, rather than the new Victorian-built model prisons. Using the CLiC (Corpus Linguistics in Context) web app, which combines a set of corpora with tools to access and search sets of texts, we set out to accumulate a substantial amount of textual evidence for a description of the carceral characteristics of Dickens’s prisons. These characteristics describe features of the prison building, prison TimeSpace, prison life, and effects of the prison. Our findings present a valuable platform from which to consider the enduring popularity of the Dickensian prison in contemporary penal discourse.
CRIS-Team Scopus Importer:2024-03-27
Keywords: carceral; confinement; corpus stylistics; Dickens; imprisonment; prison

Dickens, the suspended quotation and the corpus - Mahlberg, Michaela; Smith, Catherine (Language and Literature, 2012)
This article presents a computer-assisted approach to the study of character discourse in Dickens. It focuses on the concept of the 'suspended quotation'-the interruption of a character's speech by at least five words of narrator text. After an outline of the concept of the suspended quotation as introduced by Lambert (1981), the article compares manually derived counts for suspensions in Dickens with automatically generated figures. This comparison shows how corpus methods can help to increase the scale at which the phenomenon is studied. It highlights that quantitative information for selected sections of a novel does not necessarily represent the patterns that are found across the whole text. The article also includes a qualitative analysis of suspensions. With the help of the new tool CLiC, it investigates interruptions of the speech of Mrs Sparsit in Hard Times and illustrates how suspensions can be useful places for the presentation of character information. CLiC is further used to find patterns of the word pause that provide insights into how suspensions contribute to the representation of pauses in character speech. © 2012 The Author(s).
CRIS-Team Scopus Importer:2024-03-27
Keywords: Character discourse; corpus stylistics; Dickens; suspended quotation

Editor's note - Mahlberg, Michaela (International Journal of Corpus Linguistics, 2015)
CRIS-Team Scopus Importer:2024-03-27

Exploring narrative fiction: corpora and digital humanities projects - Mahlberg, Michaela; Wiegand, Viola (The Routledge Handbook of Corpus Linguistics, 2022)
The corpus linguistic study of narrative fiction is not a simple application of existing corpus methods to just another set of texts. It requires consideration of the properties of the texts under analysis, as well as the nature of the questions that can be addressed. The focus of this chapter is on novels as a specific type of narrative fiction. The chapter is particularly concerned with how corpus methods can be used to study novels as fiction, i.e. with an emphasis on the fictional worlds in the texts rather than exclusively on the linguistic features that define a register compared to other registers. The chapter outlines a variety of approaches to fiction by relating corpora to other digital resources and considers how to narrow down a starting point for a corpus linguistic study. To understand what corpus linguistics can do for the study of novels, the chapter reflects on what is special about narrative fiction and discusses patterns and functions of the verb form looking as an example of body language descriptions of fictional characters. The chapter concludes by considering directions for the future of corpus research and its relationship to the wider digital humanities.
CRIS-Team Scopus Importer:2024-03-27

Exploring text-initial words, clusters and concgrams in a newspaper corpus - O'Donnell, Matthew Brook; Scott, Mike; Mahlberg, Michaela; Hoey, Michael (Corpus linguistics and linguistic theory, 2012)
The notion of textual colligation predicts that certain lexical items have a tendency to occur at particular points in a text, i.e. the beginning or end of texts, paragraphs or sentences. This paper describes new corpus-based methods developed to identify the profile of words, clusters (n-grams) and concgrams (non-contiguous patterns in variant order) in terms of their most common textual locations. Groups of co-occurring text-initial items are then analyzed in terms of their discourse function in relation to theories of newspaper structure. This analysis illustrates how methods from corpus linguistics, when targeted to specific textual positions, can complement text-linguistic analyses. © 2012 Walter de Gruyter.
CRIS-Team Scopus Importer:2024-03-27
Keywords: concgrams; keyness analysis; newspaper discourse; text structure; textual colligation; WordSmith Tools

Gendered body language in children’s literature over time - Čermáková, Anna; Mahlberg, Michaela (Language and Literature, 2022)
In this paper, we study gendered patterns of body language descriptions in children’s fiction. We compare a corpus of 19th-century children’s literature with a corpus of contemporary fiction for children. Using a corpus linguistic approach, we study gendered five-word body part clusters, that is, repeated sequences of words that contain at least one body part noun and a marker of gender. Our aim is to identify and describe differences between the description of male and female body language across both corpora. We find that in the 19th century, there are not only fewer clusters for female characters, but the functional range of these clusters is also limited. The contemporary data suggests a trend for male and female clusters to become more similar with the clusters illustrating an increasing range of options for the description of female characters and their interactional spaces.
CRIS-Team Scopus Importer:2024-03-27
Keywords: body language; characterisation; children’s literature; fiction corpora; gender

Gender inequality and female body language in children's literature - Crossed Čermáková, Anna; Mahlberg, Michaela (Digital Scholarship in the Humanities, 2020)
In this paper, we aim to situate corpus linguistic approaches to literary texts within the wider context of digital humanities. With an exploratory case study of gendered body language in children's literature, we illustrate the relationship between quantitative and qualitative analysis. The case study is focused on female body language descriptions and how the presentation of body language has changed over time. We work with two corpora of children's literature: 19th century and contemporary fiction. Our analysis confirms the substantial imbalance in the representation of female and male characters that has been identified by earlier studies and also shows a more nuanced picture of emerging subtle changes.
CRIS-Team Scopus Importer:2024-03-27

Grammatical configuration - Mahlberg, Michaela (Cambridge University Press, 2015)
Research in literary stylistics analyses linguistic features of texts to explain literary or aesthetic effects as perceived by readers. The value of such an approach is, as Carter (1982: 67) points out, that ‘some linguistic analysis of a literary text is essential if something other than a merely intuitive or impressionistic account of the story is to be given’. It will depend on the text under investigation which linguistic categories and frameworks are most useful for the task; as analysts, we have ‘the full array of language models at our disposal’ (Simpson 2004: 3). In spite of the range of choice, there are some basic units and levels of language description that are typically drawn on in stylistic analyses. For most approaches to grammar a fundamental assumption about the relationship of linguistic units is expressed through the ‘rank scale’. According to the rank scale, larger linguistic units consist of smaller ones. On this scale, morphemes are the smallest meaningful units of grammar and from there units move up to clauses The linguistic units relate to the levels of linguistic description or branches of linguistics: morphology deals with the structure of words, lexicology with the vocabulary of a language, and grammar or syntax accounts for how words combine into phrases and clauses. Depending on the approach, terminology may vary as to whether something is called a noun ‘phrase’ or a noun ‘group’. How a rank scale is perceived to continue above the clause is also a matter for debate. Sometimes sentences are regarded as units above clauses, which already highlights limitations of a neat and tidy account of grammatical units, as a definition of the ‘sentence’ is more readily applicable to written than to spoken language. And if the sentence was an acceptable unit, would there be any textual unit above it, so that branches of linguistics like text linguistics could be accommodated as well?.
CRIS-Team Scopus Importer:2024-03-27

International Journal of Corpus Linguistics: Editorial - Mahlberg, Michaela (International Journal of Corpus Linguistics, 2009)
CRIS-Team Scopus Importer:2024-03-27

Introduction: On context and culture in corpus linguistics - Wiegand, Viola; Mahlberg, Michaela (De Gruyter, 2019)
CRIS-Team Scopus Importer:2024-03-27

Key words and translated cohesion in Lovecraft's At the Mountains of Madness and one of its Italian translations - Mastropierro, Lorenzo; Mahlberg, Michaela (English Text Construction, 2017)
In this paper, we explore the potential of a corpus approach to study translated cohesion. We use key words as starting points for identifying cohesive networks in Lovecraft's At the Mountains of Madness and discuss how these networks contribute to the construction of literary meanings in the text. We focus on the role of repetition as a key element in establishing cohesive networks between lexical items. We specifically discuss the implications of our method for the analysis of cohesion in translated texts. A comparison of Lovecraft's original novel and a translation into Italian provides us with a nuanced understanding of the complex nature of cohesive networks. Finally, we discuss the broader issue of applying models and methods from corpus linguistics to corpus stylistic analysis.
CRIS-Team Scopus Importer:2024-03-27
Keywords: Cohesive networks; Corpus stylistics; Key words; Literary translation; Lovecraft

Language and COVID-19: Corpus linguistics and the social reality of the pandemic - Mahlberg, Michaela; Brookes, Gavin (International Journal of Corpus Linguistics, 2021)
CRIS-Team Scopus Importer:2024-03-27

Literary style and literary texts - Mahlberg, Michaela (Cambridge University Press, 2015)
According to Leech (2008: 55), “[t]he study of style is essentially the study of variation in the use of language” (emphasis in the original). The study of style in literary texts is typically seen as the remit of literary stylistics. In the same way that corpus-linguistic methods are increasingly used in a range of linguistic and language-related fields, there is also growing interest in the application of corpus methods to the study of literary texts. Over the past decade, the use of the term “corpus stylistics” has reflected this growing interest. Sometimes the term corpus stylistics indicates a disciplinary background out of which a particular study has developed. However, Biber (2011: 20) critically observes that the “spin on the historical development of corpus-stylistic research disregards the long tradition of computational and statistical research on authorship attribution and literary style.” In this chapter I want to make a case for the conceptualization of corpus stylistics so that the term can serve to deliberately position work in a particular research context. For a meaningful approach to corpus stylistics it is important to discuss its relationship with related fields both in terms of methodologies and explanatory purposes. Corpus stylistics is the study of literary texts that employs corpus-linguistic methods to support the analysis of textual meanings and the interpretation of texts. As such, corpus-stylistic research makes it possible to focus on individual texts and even text extracts - as the places where the aesthetic effects of language are best analyzed (Leech and Short 2007: 11). Crucial for corpus-stylistic work in this sense is the intrinsic explanatory purpose of the linguistic analysis. Leech (2008: 54) distinguishes between “descriptive” and “explanatory” stylistics. For the former “the purpose is just to describe the style” and for the latter “the purpose is to use stylistics to explain something” (Leech 2008: 54).
CRIS-Team Scopus Importer:2024-03-27

Literary stylistics - Mahlberg, Michaela; Wiegand, Viola (Taylor and Francis, 2020)
CRIS-Team Scopus Importer:2024-03-27

Local textual functions of move in newspaper story patterns - Mahlberg, Michaela (Studies in Corpus Linguistics, 2009)
The article investigates the link between lexical and textual patterns in newspaper texts. Patterns in newspaper stories strikingly illustrate the relationship between meaning and form. The article presents an analysis of the core move follow* in a corpus of Guardian newspaper texts. The analysis looks at the distribution of move follow* across different sections of the newspaper, it describes the meanings that follow the move pattern, and it investigates the textual positions of the pattern in the newspaper articles. It is shown that the move pattern has a tendency to occur at the beginning of a paragraph and has a preference for the second paragraph in an article. The textual positions of the pattern are linked to the news values that characterise a story. By drawing on the concept of local textual functions and White's (1997) approach to the structure of newspaper articles, the analysis illustrates how corpus linguistic and textlinguistic approaches can complement one another.
CRIS-Team Scopus Importer:2024-03-27

Mind-modelling with corpus stylistics in David Copperfield - Stockwell, Peter; Mahlberg, Michaela (Language and Literature, 2015)
We suggest an innovative approach to literary discourse by using corpus linguistic methods to address research questions from cognitive poetics. In this article, we focus on the way that readers engage in mind-modelling in the process of characterisation. The article sets out our cognitive poetic model of characterisation that emphasises the continuity between literary characterisation and real-life human relationships. The model also aims to deal with the modelling of the author's mind in line with the modelling of the minds of fictional characters. Crucially, our approach to mind-modelling is text-driven. Therefore we are able to employ corpus linguistic techniques systematically to identify textual patterns that function as cues triggering character information. In this article, we explore our understanding of mind-modelling through the characterisation of Mr. Dick from David Copperfield by Charles Dickens. Using the CLiC tool (Corpus Linguistics in Cheshire) developed for the exploration of 19th-century fiction, we investigate the textual traces in non-quotations around this character, in order to draw out the techniques of characterisation other than speech presentation. We show that Mr. Dick is a thematically and authorially significant character in the novel, and we move towards a rigorous account of the reader's modelling of authorial intention.
CRIS-Team Scopus Importer:2024-03-27
Keywords: Character; CLiC; cognitive poetics; corpus stylistics; David Copperfield; Dickens; mind-modelling; Mr. Dick; suspensions; Theory of Mind

Opportunities in the new decade - Mahlberg, Michaela; Busse, Beatrix (International Journal of Corpus Linguistics, 2020)
CRIS-Team Scopus Importer:2024-03-27

Phrases in literary contexts: Patterns and distributions of suspensions in Dickens's novels - Mahlberg, Michaela; Smith, Catherine; Preston, Simon (International Journal of Corpus Linguistics, 2013)
This paper addresses relations between lexico-grammatical patterns and texts. Our focus is on a specific linguistic unit, the 'suspended quotation' (or 'suspension'), which has received particular attention in Dickens studies. The suspended quotation refers to an interruption of a fictional character's speech by the narrator with a sequence of at least five words. We show how corpus linguistic methods can help to systematically study suspensions in a corpus of Dickens's novels: we investigate relationships between patterns of body language presentation and suspensions; we consider the distribution of suspensions across novels; and we illustrate how patterns in suspensions relate to meanings of reporting verbs. Overall, we argue that suspensions are discernible units that contribute to meaningful patterns in narrative prose. © John Benjamins Publishing Company.
CRIS-Team Scopus Importer:2024-03-27
Keywords: Body language presentation; Dickens; Reporting verbs; Suspended quotation; Suspension annotation

Reading Dickens's characters: Employing psycholinguistic methods to investigate the cognitive reality of patterns in texts - Mahlberg, Michaela; Conklin, Kathy; Bisson, Marie Josée (Language and Literature, 2014)
This article reports the findings of an empirical study that uses eye-tracking and follow-up interviews as methods to investigate how participants read body language clusters in novels by Charles Dickens. The study builds on previous corpus stylistic work that has identified patterns of body language presentation as techniques of characterisation in Dickens (Mahlberg, 2013). The article focuses on the reading of 'clusters', that is, repeated sequences of words. It is set in a research context that brings together observations from both corpus linguistics and psycholinguistics on the processing of repeated patterns. The results show that the body language clusters are read significantly faster than the overall sample extracts which suggests that the clusters are stored as units in the brain. This finding is complemented by the results of the follow-up questions which indicate that readers do not seem to refer to the clusters when talking about character information, although they are able to refer to clusters when biased prompts are used to elicit information. Beyond the specific results of the study, this article makes a contribution to the development of complementary methods in literary stylistics and it points to directions for further subclassifications of clusters that could not be achieved on the basis of corpus data alone.
CRIS-Team Scopus Importer:2024-03-27
Keywords: awareness; characterisation; clusters; Corpus stylistics; Dickens; eye-tracking; psycholinguistics; reading times

Responding Effectively to Customer Feedback on Twitter: A Mixed Methods Study of Webcare Styles - Fuoli, Matteo; Clarke, Isobelle; Wiegand, Viola; Ziezold, Hendrik; Mahlberg, Michaela (Applied Linguistics, 2021)
Social media offer an unprecedented opportunity for companies to interact more closely with customers and market their products and services. But social media also present reputational risks as negative word-of-mouth can spread more quickly and widely through these platforms than ever before. This study investigates how companies respond to customer complaints on Twitter. We propose an innovative mixed methods approach (i) to identify the key features that mark the styles used by a sample of companies in their replies to customers and (ii) to determine the most effective strategies for responding to complaints. Our results reveal that an affective style, expressed through devices such as stance markers, emphatics, and amplifiers, elicits the most positive response from complainants, regardless of the formality of the message. The study advances our understanding of the features and effects of corporate social media discourse. It also provides business communication practitioners with linguistically grounded insights that can inform the development of appropriate strategies for dealing with negative word-of-mouth online.
CRIS-Team Scopus Importer:2024-03-27

Speech-bundles in the 19th-century English novel - Mahlberg, Michaela; Wiegand, Viola; Stockwell, Peter; Hennessey, Anthony (Language and Literature, 2019)
We propose a lexico-grammatical approach to speech in fiction based on the centrality of ‘fictional speech-bundles’ as the key element of fictional talk. To identify fictional speech-bundles, we use three corpora of 19th-century fiction that are available through the corpus stylistic web application CLiC (Corpus Linguistics in Context). We focus on the ‘quotes’ subsets of the corpora, i.e. text within quotation marks, which is mostly equivalent to direct speech. These quotes subsets are compared across the fiction corpora and with the spoken component of the British National Corpus 1994. The comparisons illustrate how fictional speech-bundles can be described on a continuum from lexical bundles in real spoken language to repeated sequences of words that are specific to individual fictional characters. Typical functions of fictional speech-bundles are the description of interactions and interpersonal relationships of fictional characters. While our approach crucially depends on an innovative corpus linguistic methodology, it also draws on theoretical insights into spoken grammar and characterisation in fiction in order to question traditional notions of realism and authenticity in fictional speech.
CRIS-Team Scopus Importer:2024-03-27
Keywords: 19th-century fiction; characterisation; CLiC; corpus linguistics; lexical bundles; realism; spoken grammar

The corpus stylistic analysis of fiction - Or the fiction of corpus stylistics? - Mahlberg, Michaela (Language and Computers, 2012)
This paper argues that corpus stylistics can contribute methodologies and concepts to support the investigation of character information in fiction. Focusing on Charles Dickens, the paper looks at lexicogrammatical patterns as well as places in the literary text. It suggests that clusters, i.e. repeated sequences of words, and suspensions, i.e. interruptions of characters' speech by the narrator, can serve as textual cues in the process of characterization. These concepts are illustrated with examples for the characters Bucket and Tulkinghorn in Bleak House. The analysis of the examples leads to an outline of challenges for corpus stylistics that result from the need to interpret features on the textual surface in relation to the effects they might have on the processing of the text by readers.
CRIS-Team Scopus Importer:2024-03-27

The representation of mothers and the gendered social structure of nineteenthcentury children's literature - Čermakova, Anna; Mahlberg, Michaela (English Text Construction, 2021)
Language has the capacity to create fictional worlds and to describe real-life social structures. In this paper, we explore gendered social structures in a corpus of nineteenth-century children's fiction. We describe these structures in terms of the frequent nouns that are used to label people in the texts of the corpus. Through a bottom-up categorisation of these nouns into four groups, we find, in line with previous studies, textual evidence of a society that is unequal and that is divided into a private and a public sphere. Our study focuses in particular on mothers, the most frequent character type in children's fiction. The representation of mothers includes abstract qualities, such as a mother's love, as well as concrete behaviours, such as mothers taking their children into their arms. Both types of qualities contribute to the depiction of mothers as an anchor point for the private sphere.
CRIS-Team Scopus Importer:2024-03-27
Keywords: Corpus stylistics; Gender; General nouns; Norms; Victorian literature

Translating fictional characters – Alice and the Queen from the Wonderland in English and Czech - Čermáková, Anna; Mahlberg, Michaela (John Benjamins Publishing Company, 2018)
In this chapter, we propose a novel theoretical framework for the literary translation of fictional characters. This framework develops the cognitive corpus linguistic notion of mind-modelling to account for process-, product- and function-oriented aspects of literary translation. We use the examples of Alice and the Queen from Alice’s Adventures in Wonderland to compare character cues across the English original and a Czech translation. The character cues we focus on are reporting verbs. Reporting verbs, as part of the presentation of fictional speech, form a central component of narrative fiction and so provide an ideal evidential basis for our theoretical framework. The translation shifts we found through our comparison of source and target text specifically include gendered uses of reporting verbs. By approaching the target text as both a translation and a reading of the text in its own right we are able to view translation shifts as a reflection of shifts in the mind-modelling of fictional characters.
CRIS-Team Scopus Importer:2024-03-27